Delayed CPAP-Induced Pneumocephalus and Meningitis Posttranssphenoidal Surgery - Tara D’Ignazio; Mary Francispillai; Marc Giroux; Martin Albert (Case Reports in Critical Care)
Transsphenoidal surgery (TSS) is a frequently used technique to remove pituitary adenomas. Rare complications of TSS include development of postoperative pneumocephalus. Many patients undergoing TSS also suffer from obstructive sleep apnea (OSA) and thus require positive pressure ventilation. The exact timing of when to safely reintroduce the CPAP machine in this subset of patients is presently not exactly known but is most often cited as being two to four weeks postoperatively. In this case, we describe the story of a 69-year-old female who underwent TSS for a nonsecreting pituitary adenoma in April 2012 and went on to develop pneumocephalus five weeks postoperatively after reintroduction of her CPAP machine. This is the latest presentation of pneumocephalus after reintroduction of CPAP documented in present literature. The case reopens the debate as to how many weeks postoperatively positive pressure ventilation should be withheld to prevent the development of pneumocephalus in patients having undergone TSS with simultaneous OSA.